2002
DOI: 10.2190/569a-xlpx-yf5c-h9hu
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Patent Medicine Sellers in Home Management of Childhood Malaria: A Situational Analysis of Experience in Rural Nigeria

Abstract: Patent medicine sellers (PMS) play an important role in supplying the medication needs of the community particularly antimalaria. A situational analysis of the role of PMS in home management of malaria was carried out in four rural local government areas in Southwestern Nigeria using both cross sectional and observational study methods. The results showed that patent medicine stores constituted 76.2% of the medicine shops in the areas. The PMS provided not only drugs but also consultation services. Malaria con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 3 publications
(3 reference statements)
1
12
0
Order By: Relevance
“…A single study of dispensing practices for non-malaria illnesses found that 69% of PPMVs reported ORS as their first-line treatment for diarrhea in under-fives [ 48 ]. The reliance of these studies on self-reported data may overstate rates of proper treatment; a study comparing self-reported to observed dispensing practices for child malaria found that PPMVs under-reported dispensing of improper treatments [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A single study of dispensing practices for non-malaria illnesses found that 69% of PPMVs reported ORS as their first-line treatment for diarrhea in under-fives [ 48 ]. The reliance of these studies on self-reported data may overstate rates of proper treatment; a study comparing self-reported to observed dispensing practices for child malaria found that PPMVs under-reported dispensing of improper treatments [ 75 ].…”
Section: Resultsmentioning
confidence: 99%
“…Nineteen articles assessed the interactions between PPMVs and their clients ( Table 1 ), focusing on drug choice, consultation about the illness, and instructions regarding drug administration. Interactions about drug choice, and the majority of drug sales, were largely driven by customer demand for specific drugs [ 37 , 38 , 44 , 49 , 70 , 75 , 76 ]. Although some PPMVs report that customers ask for recommendations on drug choice, particularly for sick children [ 75 ] and anti-malarial drugs [ 37 , 38 ], observational data showed that PPMVs only suggested drug choices in 31% of encounters [ 21 ], and that between 58% and 69% of PPMVs sold drugs as requested without asking the customer for any clarification [ 21 , 60 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Nigeria, malaria is holoendemic (Bruce-Chwatt, 1983). It is worst hit in the poorest countries and those under difficult and impoverished conditions (WHO, 1987;Uko et al, 1994) and accounts for about 1 million episodes annually with a mortality rate of 1% (Ajayi et al, 1995). About four species of Plasmodium have been found to commonly infect man.…”
Section: Introductionmentioning
confidence: 99%
“…The iCCM strategy has led to the removal of amoxicillin DT from the prescription-only medicine list to enable the PPMVs to have access to the drug for the treatment of non-severe childhood pneumonia at the community level [5]. In Nigeria, this decision was also supported by the fact that majority of the populace in rural areas visit PPMVs for medical advice, diagnosis, medications and general health management due to their low service cost and accessibility [6,7]. A study in Uganda has also shown that PPMVs are indispensable at the rural communities [8].…”
Section: Introductionmentioning
confidence: 99%